Cross-Sectional Capital Market Research and Model Specification. - Landsman, Wayne R.; Magliolo, Joseph (The Accounting Review, 1988)
ABSTRACT: This paper examines the Issue of model specification in cross-sectional capital market research. In particular, it is argued that the decision of whether to select a price level or price change (return) specification is a joint function of (1) the economic model of equilibrium that is assumed; and (2) the nature of the econometric properties of the data that cause OLS assumptions to be violated. The historical origins of the model specification debate are traced to focus on three compelling reasons for selecting a returns-based methodology. We conclude that the relative advantages of returns and levels methodologies are dependent upon the set of assumptions maintained by the researcher regarding the pricing relation and the econometric properties of the data used for estimation. We provide examples and an Interpretation of extant accounting capital market research to help illustrate our conclusions.